PENAFSIRAN KONSTITUSI DALAM PENGUJIAN KONSTITUSIONALITAS UNDANG- UNDANG TERHADAP UNDANG- UNDANG DASAR 1945 - Lailam, Tanto (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
This study is about interpretation of constitution, this study is based on the extent authority of the Constitutional Court on theÂ interpretation ofÂ the constitution,Â including various verdicts that are considered as controversial.The result of the study shows that Constitution 1945 giving authority of the constitutionÂ interpretation of the Constitutional Court to evaluate the conflict ofÂ legal norm, this could be meant that the Constitutional Court is âthe guardian ofÂ the constitution and the sole interpreting of constitutionâ and as the legitimate interpreter ofÂ the constitution.Â SomeÂ interestingÂ in implementingÂ theÂ interpretation ofÂ the constitution as aÂ standardÂ toevaluateÂ the conflict ofÂ legal norm, consists of: First, essentially,Â that theÂ interpretation ofÂ the constitutionÂ is one of the ways to elaborate understandings contained in constitution text. Second, related to the independence and theÂ freedom of judge in using an interpretation method whichÂ is notÂ regulated by positiveÂ law, therefore the judge isÂ free to use those interpretation methods which are appropriate with the conviction of the Justice. JusticeÂ inÂ usingÂ theÂ interpretation methodÂ doesnâtÂ onlyÂ haveÂ functionÂ asÂ funnel ofÂ theÂ act,Â butÂ alsoÂ has functioned as the funnel of justice since a judge is required the value of the law and the sense of justice which exists in the society (substantial justice). Refer toÂ the theory of living constitution, therefore Constitution 1945 should beÂ understoodÂ asÂ aÂ constitution which hasÂ textualÂ andÂ contextualÂ dimentionÂ Third,Â theÂ restrictionÂ in using the interpretation method, the constitutional judge couldnât only focused into the originalism interpretation method whichÂ onlyÂ basedÂ toÂ originalÂ intentÂ /Â theÂ formulationÂ ofÂ ConstitutionÂ 1945Â orÂ usingÂ theÂ other interpretationsÂ (nonÂ originalist) which oppositelyÂ thoseÂ interpretationÂ the 1945Â Constitution doesnât work according to system and/ or contended withÂ the main idea underlying the constitution itself entirelyÂ related to theÂ purpoÂ seÂ that wouldÂ likeÂ to beÂ realized.Â Fourth,Â theÂ use ofÂ interpretation methodÂ shouldÂ beÂ ableÂ toÂ be accounted toÂ the publics, therefore the validity could be examinedÂ in certain cases. This is very essential to dosince Constitutional Court has an extent interpretation authority so that it could keep justice of Constitutional CourtÂ to avoid it from misuse of authorityÂ in interpreting of 1945 Constitution.